The art of black and white photography techniques for creating superb images in a digital workflow - Hoffmann, Torsten Andreas 1956- (Rocky Nook, 2012)
"Over the last few years, most books on photography have been focused on the new breed of cameras and how to master the digital imaging workflow. In The Art of Black and White Photography author and photographer Torsten Andreas Hoffmann takes a different approach, focusing on image composition and image capture, with an emphasis on the creative aspects of black and white photography rather than on the digital workflow. After introducing the ground rules of composition, Hoffmann illustrates their applications with his own stunning black and white images that cover various photographic genres, including architecture, street photography, portraiture, and surreal photography. Also discussed are the elements of a "photographic language"', which distinguishes creative photography from random shooting. Finally, you will learn valuable post-processing techniques, mostly using Photoshop, that emphasize the functions necessary for creating outstanding black and white images. This second edition has been updated to include Photoshop CS5, as well as brand new images, content, and a revised layout"--
Includes bibliographical references and index. - Print version record
Keywords: Photography -- Digital techniques; Black-and-white photography; Photographie numérique; Photographie en noir et blanc; black-and-white photography; PHOTOGRAPHY; Reference; PHOTOGRAPHY; General; PHOTOGRAPHY; Techniques; Darkroom; PHOTOGRAPHY; Techniques; General; PHOTOGRAPHY; Techniques; Digital (see also COMPUTERS; Digital Media; Photography); ART; Film & Video; PHOTOGRAPHY; Techniques; Cinematography & Videography; Photography; Digital techniques